Pengaruh Rasio Keuangan terhadap Financial Distress pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bei Tahun 2019-2024 - Clarentia Agustin Christie Ziliwu; Amalia, Naili (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the effect of financial ratios on financial distress in transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The research employed a documentation method by collecting secondary data from the companies’ financial statements within the observed period. The financial ratios analyzed include profitability, liquidity, leverage, and activity. The level of financial distress was measured using the Altman Z-Score method. The sample was selected using a purposive sampling technique, consisting of 22 companies observed over six years. Data analysis was conducted using panel data regression with the assistance of EViews 12, with the selected model being the Fixed Effect Model (FEM). The partial test results indicate that profitability, liquidity, leverage, and activity ratios do not have a significant effect on financial distress. However, the simultaneous test results show that the four variables together significantly affect financial distress. These findings suggest that financial ratios cannot serve as a single indicator in assessing a company’s financial distress. Nevertheless, when used collectively and combined with the Altman Z-Score measurement, they can provide a more accurate assessment of a company’s financial distress condition.